Composite material and preparation method and application thereof

By depositing oxygen-containing TaC coatings and TaC coatings on the surface of the substrate, the problem of difficult grain size of tantalum carbide coatings at lower temperatures is solved, the antioxidant performance and high temperature stability of the coating are improved, and the Product lifespan.

CN118880278BActive Publication Date: 2024-12-13湖南德智新材料股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411376307.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing tantalum carbide coatings are difficult to control grain size at lower temperatures, resulting in poor corrosion resistance and high-temperature creep performance. Too large or too small grains will affect product life and bonding performance.

Method used

The oxygen-containing TaC coating and TaC coating are deposited successively on the surface of the substrate by chemical vapor deposition method, and the oxygen content is controlled below 1000 ppm, the deposition temperature is 1100℃-1500℃, and the pressure is 1 kPa-5 kPa, using oxygen-containing The TaC layer affects the chemical composition and energy state of the grain boundary, and 10-20μm TaC grains are prepared.

Benefits of technology

Effective control of the grain size of TaC coating at lower temperatures is achieved, and the overall performance of the coating is improved, including oxidation resistance, high temperature stability, wear resistance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880278B_ABST
    Figure CN118880278B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of tantalum carbide (TaC) materials, and provides a composite material and a preparation method and application thereof, the method comprising chemical vapor deposition of an oxygen-containing TaC coating and a TaC coating on the surface of a substrate in sequence; the gas system for depositing the oxygen-containing TaC coating comprises a Ta source, a C source, an O source, a reducing gas and a diluent gas, and the amount of the O source introduced makes the oxygen content of the oxygen-containing TaC coating by weight less than 1000 ppm; the conditions for depositing the oxygen-containing TaC coating and the TaC coating respectively include: a deposition temperature of 1100°C ‑1500°C, and a pressure of 1 kPa ‑5 kPa. The method can prepare a TaC coating with a moderate and uniform grain size at a relatively low temperature, the coating has a higher density, and has better high temperature stability and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tantalum carbide materials, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] TaC ceramic is an ultra-high temperature material with excellent physical properties such as high hardness, high melting point (3950℃), excellent thermal conductivity and electrical conductivity, as well as strong resistance to chemical erosion and oxidation. TaC-coated graphite susceptors prepared by chemical vapor deposition have advantages in shape formation freedom and stress tolerance. Based on its good properties, TaC coating has a wide range of application prospects in the growth of semiconductor materials, making it a very attractive anti-ablation coating in high-temperature applications.

[0003] At present, the deposition temperature of tantalum carbide coatings is prepared at a temperature of 1700°C or above. Because the grains in the tantalum carbide coatings deposited at lower temperatures are small, it is difficult to effectively control the grain size. Moreover, in general, the smaller the grains, the easier it is to oxidize, and the worse the corrosion resistance and high-temperature creep performance, resulting in a shorter product life. In addition, excessively large grains (greater than 50μm) will lead to deteriorated bonding performance and a shorter life, and the coating is prone to shedding. How to achieve grain size control of tantalum carbide coatings based on chemical vapor deposition to prepare larger grains that are easier to control and more uniform is an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a composite material and a preparation method and application thereof. The method described in the present invention can effectively control the grain size of the deposited coating at a relatively low temperature (1100°C -1500°C), prepare TaC grains of larger size (10-20μm), and the composite material has better antioxidant properties and high temperature stability.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a composite material, which comprises chemically vapor depositing an oxygen-containing TaC coating and a TaC coating on the surface of a substrate in sequence to obtain the composite material; the gas system for depositing the oxygen-containing TaC coating comprises a Ta source, a C source, an O source, a reducing gas and a diluent gas, and the amount of the O source introduced makes the content of oxygen in the oxygen-containing TaC coating by weight less than 1000 ppm; the conditions for depositing the oxygen-containing TaC coating comprise: a deposition temperature of 1100°C-1500°C and a pressure of 1 kPa-5 kPa; the gas system for depositing the TaC coating comprises a Ta source, a C source, a reducing gas and a diluent gas; the conditions for depositing the TaC coating comprise: a deposition temperature of 1100°C-1500°C and a pressure of 1 kPa-5 kPa; and the conditions for depositing the oxygen-containing TaC coating and depositing the TaC coating make the oxygen-containing TaC coating account for 10-50% of the total thickness of the oxygen-containing TaC coating and the TaC coating.

[0006] A second aspect of the present invention provides a composite material, wherein the composite material is a composite material prepared by the preparation method described in the first aspect.

[0007] A third aspect of the present invention provides a composite material, comprising a substrate and a composite coating located on the surface of the substrate, wherein the composite coating comprises an oxygen-containing TaC coating adjacent to the substrate and a TaC coating located on the other side of the oxygen-containing TaC coating; the content of oxygen in the oxygen-containing TaC coating is less than 1000 ppm by weight; in the TaC coating, the average particle size of TaC grains is 10 μm-20 μm; and the oxygen-containing TaC coating accounts for 10-50% of the total thickness of the composite coating.

[0008] The fourth aspect of the present invention provides use of the composite material described in the second aspect and the third aspect as a high temperature resistant material.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] The present invention introduces an appropriate amount of oxygen during the preparation process of the TaC coating, introduces an oxygen-containing layer into the substrate and the TaC coating, affects the chemical composition and energy state at the grain boundary, and further affects the behavior of crystal growth, so that the TaC coating containing larger grains can be deposited at a lower temperature and a lower pressure, effectively controls the grain size of the TaC coating, obtains more uniform grains, and further improves the overall performance of the coating; and the preparation method is simple and convenient to operate.

[0011] The composite coating of the present invention contains an oxygen-containing TaC coating, in which there is a trace amount of oxygen, which combines with tantalum to form tantalum oxide (Ta 2 O 5), its melting point is 1872℃, and its thermal expansion coefficient is 6-7×10 -6 / K, slightly lower than TaC. In the working environment, the right amount of tantalum oxide makes the composite coating obtain certain plasticity, toughness and self-healing ability, so that the TaC coating on the surface is not easy to fall off, and the graphite in the substrate will not fall off easily. In addition, the composite coating also has higher density and better high-temperature stability, excellent anti-oxidation performance, and the wear resistance and service life of the TaC coating are also significantly improved.

[0012] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Shown is the XRD pattern of the TaC coating surface in the composite material prepared in Example 1.

[0014] Figure 2 Shown is a SEM image of the surface of the TaC coating in the composite material prepared in Example 1 (magnification: ×2000). DETAILED DESCRIPTION

[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0016] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0017] The first aspect of the present invention provides a method for preparing a composite material, which comprises chemically vapor depositing an oxygen-containing TaC coating and a TaC coating on the surface of a substrate in sequence to obtain the composite material; the gas system for depositing the oxygen-containing TaC coating comprises a Ta source, a C source, an O source, a reducing gas and a diluent gas, and the amount of the O source introduced is such that the content of oxygen in the oxygen-containing TaC coating by weight is less than 1000 ppm (for example, 1 ppm, 10 ppm, 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm); the conditions for depositing the oxygen-containing TaC coating include: a deposition temperature of 1100° C. to 1500° C. (for example, 1100° C., 1200° C., 1300° C., 1400° C. or 1500° C.), a pressure of 1 kPa to 5 kPa (for example, 1 kPa, 2 kPa, 3 kPa, 4 kPa, 5 kPa, 6 kPa, 7 kPa, 8 kPa, 9 kPa, 10 kPa, 11 kPa, 12 kPa, 13 kPa, 14 kPa, 15 kPa, 16 kPa, 17 kPa, 18 kPa, 19 kPa, 20 kPa, 21 kPa, 22 kPa, 23 kPa, 24 kPa, 25 kPa, 26 kPa, 27 kPa, 28 kPa, 29 kPa, 30 kPa, 31 kPa, 32 kPa, 33 kPa, 34 kPa, 35 kPa, 36 kPa, 37 kPa, 38 kPa, 39 kPa, 4 kPa); the gas system for depositing the TaC coating includes a Ta source, a C source, a reducing gas and a diluent gas; the conditions for depositing the TaC coating include: a deposition temperature of 1100°C-1500°C (for example, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C), and a pressure of 1 kPa-5 kPa (for example, 1 kPa, 2 kPa, 3 kPa, 4 kPa, 5 kPa); and the conditions for depositing the oxygen-containing TaC coating and depositing the TaC coating are such that the oxygen-containing TaC coating accounts for 10-50% (for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%) of the total thickness of the oxygen-containing TaC coating and the TaC coating.

[0018] It should be understood that when the deposition system contains both oxygen and hydrogen, those skilled in the art can control the contents of both gases within a safe range based on safety requirements to prevent the occurrence of dangerous situations such as explosions.

[0019] The substrate may be, for example, at least one of a carbon-based substrate, a silicon-based substrate and a SiC substrate, and may be a substrate or a substrate to which a transition layer has been attached (for example, the substrate may include a carbon-based substrate and a SiC coating attached to the carbon-based substrate).

[0020] In some embodiments, the substrate is a carbon-based substrate.

[0021] In some embodiments, the thermal expansion coefficient of the carbon-based substrate is 4×10 -6 / K -7.5×10 -6 / K, density is 1.7-2.2 g / cm 3 , the porosity is 5-25% and the grain size is less than 5μm.

[0022] In some embodiments, the carbon-based substrate is graphite (such as isostatic graphite) or carbon fiber reinforced carbon.

[0023] In some embodiments, the method further includes pre-treating the substrate before deposition, and the substrate surface may have a certain roughness and / or impurities on the substrate surface may be removed by pre-treatment. The substrate surface may have a certain roughness (Ra=0.2μm-2μm) and high cleanliness by processes including but not limited to grinding, sandblasting, plasma treatment, etc., to ensure close bonding between the coating and the substrate.

[0024] The method of removing impurities may be, for example, cleaning the substrate. The cleaning may be done by water washing, acid washing, rinsing and / or immersion, and may be done by conventional means in the art, as long as the impurities on the surface of the substrate can be removed. It should be understood that after cleaning, the substrate may be dried and then used in the subsequent deposition process. The drying method may be a conventional drying method, such as drying using a vacuum dryer or air blast (drying at 100-300°C for more than 2 hours). An oxygen-containing atmosphere may also be introduced (the oxygen concentration may be, for example, 200 ppm-500 ppm) to oxidize and remove the surface of the substrate and / or the particles on the surface or to purge and clean them.

[0025] The method for depositing the TaC coating of the present invention is CVD deposition, and the equipment used can be a CVD vapor deposition furnace. The substrate can be horizontally placed in the deposition reaction chamber, the furnace door is closed, the reaction chamber is evacuated to a vacuum below 200 Pa, and then the temperature is increased at 2°C / min-10°C / min to the deposition temperature.

[0026] In some embodiments, the Ta source gas includes TaF 5 、TaCl 5 and TaBr 5 At least one of .

[0027] In some embodiments, the C source gas comprises CH 4 , C 2 H 4 , C 2 H 6 , C 3 H 6 and C 3 H 8 At least one of .

[0028] In some embodiments, the O source comprises O 2 , H 2 O、CO 2 and CO. Sources other than oxygen can provide O during the deposition process, such as H 2O can decompose into hydrogen and oxygen under deposition conditions and participate in the reaction.

[0029] In some embodiments, the amount of the O source introduced is such that the oxygen content in the oxygen-containing TaC coating is 10 ppm to 200 ppm by weight.

[0030] In some embodiments, the proportion of the O source in the gas system is less than 1000 ppm (for example, 1 ppm, 10 ppm, 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm).

[0031] In some embodiments, the reducing gas is hydrogen.

[0032] In some embodiments, in the gas system for depositing the oxygen-containing TaC coating and depositing the TaC coating, the molar ratio of Ta element to C element is independently 1:1-2 (for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2).

[0033] In some embodiments, in the gas system for depositing the oxygen-containing TaC coating and depositing the TaC coating, the molar ratio of the Ta source to the reducing gas is independently 1:0.5-5 (eg, 0.5, 1, 2, 3, 4, 5).

[0034] In some embodiments, the diluent gas may be an inert gas, that is, a gas that does not react with other components, such as argon Ar or helium He.

[0035] In some embodiments, in the gas system for depositing the oxygen-containing TaC coating and depositing the TaC coating, the molar ratio of the Ta source to the diluent gas is independently 1:10-100 (eg, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100).

[0036] In some embodiments, the conditions for depositing the oxygen-containing TaC coating include: a deposition time of 0.5-2 h, such as 0.5 h, 1 h, 1.5 h, and 2 h.

[0037] In some embodiments, the conditions for depositing the TaC coating include: a deposition time of 2-4 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, and 4 hours.

[0038] After the final product is obtained, a vacuum cooling operation can be performed. The specific operation method can be a conventional operation method in the art. For example, after the last deposition is completed, the furnace can be evacuated to below 200 Pa, and the temperature can be gradually reduced to room temperature at a cooling rate of 2-10 ° C / min, and then 20-200 L / min of Ar or N can be introduced.2 The pressure is adjusted to normal pressure, and then the furnace is opened to take out the product.

[0039] A second aspect of the present invention provides a composite material, wherein the composite material is a composite material prepared by the preparation method described in the first aspect.

[0040] For the description of the composite material, please refer to the third aspect.

[0041] A third aspect of the present invention provides a composite material, comprising a substrate and a composite coating located on the surface of the substrate, wherein the composite coating comprises an oxygen-containing TaC coating adjacent to the substrate and a TaC coating located on the other side of the oxygen-containing TaC coating; the content of oxygen in the oxygen-containing TaC coating is less than 1000 ppm by weight (for example, 1 ppm, 10 ppm, 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm); in the TaC coating, the average particle size of TaC grains is 10 μm-20 μm; and the oxygen-containing TaC coating accounts for 10-50% (for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%) of the total thickness of the composite coating.

[0042] In the present invention, the oxygen content in the oxygen-containing TaC layer can be measured by an oxygen, nitrogen and hydrogen analyzer.

[0043] In the present invention, the grain size can be measured and calculated by observing the coating surface with an optical microscope or a scanning electron microscope and using Image J software.

[0044] In some embodiments, the oxygen-containing TaC coating contains 10 ppm to 200 ppm of oxygen by weight.

[0045] In some embodiments, the surface of the TaC coating includes characteristic diffraction peaks of (200) crystal plane, (220) crystal plane, (111) crystal plane, (311) crystal plane, (222) crystal plane and (400) crystal plane in the spectrum obtained by XRD, and their 2θ are 39.6°-42.0°, 57.7°-59.8°, 33.8°-36.2°, 69.2°-71.2°, 73.0°-74.6° and 87.0°-88.5° respectively. The characteristic diffraction peaks of each crystal plane are independent of each other and have no overlapping parts.

[0046] In some embodiments, the intensity of the (200) crystal plane obtained by XRD on the surface of the TaC coating is (200) The strength I of the (111) crystal plane (220) Ratio I (200) / I (111)Is 1-10.

[0047] In some embodiments, I (200) / I (220) 5-30.

[0048] In some embodiments, I (111) / I (220) Is 1-5.

[0049] In some embodiments, I (200) / I (311) 5-30.

[0050] In some embodiments, I (200) / I (222) It is 10-80.

[0051] In some embodiments, I (200) / I (400) 20-150.

[0052] In some embodiments, the content of Ta element in the composite coating is 90wt%-95wt%.

[0053] In the present invention, the method for determining the content of each element is energy dispersive X-ray spectroscopy, and a point is taken in the coating area for point scanning to obtain the content of each element.

[0054] In some embodiments, the composite coating has a thickness of 20 μm-50 μm, such as 20 μm, 30 μm, 40 μm, or 50 μm.

[0055] In some embodiments, the thickness of the TaC coating is 15 μm-25 μm, such as 15 μm, 18 μm, 20 μm, 22 μm, 24 μm, or 25 μm.

[0056] In some embodiments, the oxygen-containing TaC coating has a thickness of 2 μm-25 μm, such as 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, or 25 μm.

[0057] The fourth aspect of the present invention provides use of the composite material described in the second aspect and the third aspect as a high temperature resistant material.

[0058] The composite material can be used as a semiconductor material, for example, and can be applied to the fields of single crystal growth, energy electronics, aerospace, semiconductors, energy vehicles, etc.

[0059] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The present invention is described in detail below in conjunction with specific embodiments, and these embodiments are used to understand but not limit the present invention.

[0060] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0061] In the following examples and comparative examples, the numerical value after “±” is the standard deviation of all measured values, such as: 20, 16, 12, 14, 17, 18, 16, 17, 14, 12, 13, 15, 16, 16, 16, 16, 16, 16, 16, 16, this group of data can be expressed as: 15.6±1.9.

[0062] Example 1

[0063] (1) The surface of the graphite substrate is rinsed, soaked and rinsed with deionized water to remove the graphite powder on the surface, and then vacuum dried at 120°C for 3 hours to ensure that the moisture in the substrate is completely removed; then the graphite surface is sandblasted to make the roughness Ra of the graphite substrate surface about 1 μm.

[0064] (2) Place the graphite substrate in a CVD deposition furnace, close the furnace door, evacuate the reaction chamber to below 200 Pa, raise the temperature to 1300 °C, control the pressure to 3 kPa, and stabilize it for 20 min. Then, introduce Ar. 5 , H 2 O, H 2 , Ar and CH 4 It was passed into a CVD deposition furnace and deposited for 1 hour to obtain an oxygen-containing TaC coating. 5 , CH 4 , H 2 The molar ratio of Ar is 1:1.5:3:50, and the oxygen content measured by the online oxygen content monitoring analyzer is 300±10 ppm. The content of O element in the oxygen-containing TaC coating is 100 ppm (determined by an oxygen, nitrogen and hydrogen analyzer).

[0065] (3) Then stop feeding H into the CVD deposition furnace. 2 O and CH 4 、TaCl 5 , H 2, continue to use Ar to purge the pipeline and deposition chamber for 20 minutes (to make the oxygen content lower than the detection limit of the equipment 0.1 ppm), and then TaCl 5 , H 2 , Ar and CH 4 The flow rate remains unchanged and continues to be passed into the CVD deposition furnace for 3 hours to obtain the TaC coating. 5 , CH 4 , H 2 , and the molar ratio of Ar is 1:1.5:3:50.

[0066] After the reaction was completed, the furnace was evacuated to below 200 Pa, and the temperature was gradually lowered to room temperature at a rate of 5°C / min. Ar was then introduced to adjust the pressure to normal pressure, and the furnace was opened to take out the composite material.

[0067] It was determined that the thickness of the oxygen-containing TaC coating was 10 μm, the thickness of the TaC coating was 20 μm, the Ta element content in the composite coating was 92.5 wt%, the average particle size of the TaC grains in the TaC coating was 15 ± 2 μm, and the grains had good uniformity. The XRD and SEM images of the surface of the TaC coating were as follows: Figure 1 and Figure 2 The TaC coating surface has characteristic diffraction peaks of (111) crystal plane, (200) crystal plane, (220) crystal plane, (311) crystal plane, (222) crystal plane and (400) crystal plane at 35.0°, 40.7°, 58.7°, 70.1°, 73.7° and 87.6°, respectively. (200) / I (111) is 5.7, I (200) / I (220) 16.99, I (111) / I (220) is 2.96, I (200) / I (311) is 17.56, I (200) / I (222) is 51.34, I (200) / I (400) It is 116.46.

[0068] Example 2

[0069] (1) The surface of the graphite substrate is rinsed, soaked and rinsed with deionized water to remove the graphite powder on the surface, and then vacuum dried at 120°C for 3 hours to ensure that the moisture in the substrate is completely removed; then the graphite surface is sandblasted to make the roughness Ra of the graphite substrate surface about 1 μm.

[0070] (2) Place the graphite substrate in a CVD deposition furnace, close the furnace door, evacuate the reaction chamber to below 200 Pa, raise the temperature to 1200 °C, control the pressure to 2 kPa, and introduce Ar for 20 min, then add TaCl 5 , O 2 , H 2 , Ar and CH 4 It was passed into a CVD deposition furnace and deposited for 2 hours to obtain an oxygen-containing TaC coating. 5 , CH 4 , H 2 The molar ratio of Ar is 1:1.5:3:50, and the oxygen content measured by the online oxygen content monitoring analyzer is 280±10 ppm. The content of O element in the oxygen-containing TaC coating is 90 ppm (determined by an oxygen, nitrogen and hydrogen analyzer).

[0071] (3) Then stop feeding H into the CVD deposition furnace. 2 O and CH 4 、TaCl 5 , H 2 , continue to use Ar to purge the pipeline and deposition chamber for 20 minutes (to make the oxygen content lower than the detection limit of the equipment 0.1 ppm), and then TaCl 5 , H 2 , Ar and CH 4 The flow rate remains unchanged and continues to be passed into the CVD deposition furnace for 4 hours to obtain the TaC coating. 5 , CH 4 , H 2 , and the molar ratio of Ar is 1:1.5:3:50.

[0072] After the reaction was completed, the furnace was evacuated to below 200 Pa, and the temperature was gradually lowered to room temperature at a rate of 5°C / min. Ar was then introduced to adjust the pressure to normal pressure, and the furnace was opened to take out the composite material.

[0073] The thickness of the oxygen-containing TaC coating is 10μm, the thickness of the TaC coating is 16μm, the Ta element content in the composite coating is 92.1wt%, and the average particle size of the TaC grains in the TaC coating is 12±2μm, with good uniformity.

[0074] Example 3

[0075] (1) The surface of the graphite substrate is rinsed, soaked and rinsed with deionized water to remove the graphite powder on the surface, and then vacuum dried at 120°C for 3 hours to ensure that the moisture in the substrate is completely removed; then the graphite surface is sandblasted to make the roughness Ra of the graphite substrate surface about 1 μm.

[0076] (2) Place the graphite substrate in a CVD deposition furnace, close the furnace door, evacuate the reaction chamber to below 200 Pa, raise the temperature to 1400 °C, control the pressure to 4 kPa, and introduce Ar for 20 min, then add TaCl 5 , CO 2 , H 2 , Ar and CH 4 It was passed into a CVD deposition furnace and deposited for 0.5 h to obtain an oxygen-containing TaC coating. 5 , CH 4 , H 2 The molar ratio of Ar is 1:1.5:3:50. At the same time, CO is introduced into the furnace 2 The carbon dioxide content measured by the online carbon dioxide content monitoring analyzer is 305±10ppm. The content of O element in the oxygen-containing TaC coating is 120 ppm (determined by an oxygen, nitrogen and hydrogen analyzer).

[0077] (3) Then stop feeding H into the CVD deposition furnace. 2 O and CH 4 、TaCl 5 , H 2 , continue to use Ar to purge the pipeline and deposition chamber for 20 minutes (to make the oxygen content lower than the detection limit of the equipment 0.1 ppm), and then TaCl 5 , H 2 , Ar and CH 4 The flow rate remains unchanged and continues to be passed into the CVD deposition furnace for 3 hours to obtain the TaC coating. 5 , CH 4 , H 2 , and the molar ratio of Ar is 1:1.5:3:50.

[0078] After the reaction was completed, the furnace was evacuated to below 200 Pa, and the temperature was gradually lowered to room temperature at a rate of 5°C / min. Ar was then introduced to adjust the pressure to normal pressure, and the furnace was opened to take out the composite material.

[0079] The thickness of the oxygen-containing TaC coating is 10μm, the thickness of the TaC coating is 17μm, the Ta element content in the composite coating is 93.3wt%. In the TaC coating, the average particle size of the TaC grains is 18±2μm, and the uniformity is good.

[0080] Example 4

[0081] The method described in Example 1 was followed, except that the composition of the gas system during the deposition of the coating was different.

[0082] Example 4a: During the deposition of oxygen-containing TaC coating and TaC coating, TaCl5 , CH 4 , H 2 The molar ratios of Ar are 1:1.8:5:50 respectively.

[0083] Example 4b: During the deposition of oxygen-containing TaC coating and TaC coating, TaCl 5 , CH 4 , H 2 The molar ratios of Ar are 1:1.2:3:50 respectively.

[0084] The results of the content of O element in the oxygen-containing TaC coating, the content of Ta in the TaC layer and the average particle size of TaC grains are shown in Table 1.

[0085] Example 5

[0086] The method described in Example 1 was followed, except that the oxygen content in the gas system was different when depositing the oxygen-containing TaC coating.

[0087] Example 5a: The oxygen content measured by the online oxygen content monitoring analyzer is controlled to be 620±20 ppm.

[0088] Example 5b: The oxygen content measured by the online oxygen content monitoring analyzer is controlled to be 30±2 ppm.

[0089] The results of the content of O element in the oxygen-containing TaC coating, the content of Ta in the TaC layer and the average particle size of TaC grains are shown in Table 1.

[0090] Example 6

[0091] The method described in Example 1 was followed, except that the thickness of the coating was different.

[0092] Example 6a: The thickness of the oxygen-containing TaC coating is 3 μm, and the thickness of the TaC coating is 24 μm.

[0093] Example 6b: The thickness of the oxygen-containing TaC coating is 14 μm, and the thickness of the TaC coating is 16 μm.

[0094] Comparative Example 1

[0095] The method described in Example 1 is followed, except that only the TaC layer is deposited without depositing the oxygen-containing TaC layer, and the thickness of the composite coating remains unchanged.

[0096] Comparative Example 1a: Deposition temperature 1800°C, pressure 5 kPa, TaCl 5 , CH 4 , H 2 , and the molar ratio of Ar is 1:1.1:10:20.

[0097] Comparative Example 1b: The deposition conditions are the same as those in Example 1.

[0098] Comparative Example 1c: The deposition temperature is 900° C., and the rest is the same as Example 1.

[0099] The results of Ta content in the TaC layer and the average particle size of TaC grains are shown in Table 1.

[0100] Comparative Example 2

[0101] The method described in Example 1 was followed, except that the oxygen content measured by the online oxygen content monitoring analyzer during the deposition of the oxygen-containing TaC coating was 2000 ppm.

[0102] The results of the content of O element in the oxygen-containing TaC coating, the content of Ta in the TaC layer and the average particle size of TaC grains are shown in Table 1.

[0103] Comparative Example 3

[0104] The method described in Example 1 was followed, except that the thickness of the coating was different, specifically:

[0105] Comparative Example 3a: the thickness of the oxygen-containing TaC coating is 25 μm, and the thickness of the TaC coating is 5 μm.

[0106] Comparative Example 3b: the thickness of the oxygen-containing TaC coating is 1 μm, and the thickness of the TaC coating is 30 μm.

[0107] Comparative Example 3c: No TaC coating was deposited, and the thickness of the oxygen-containing TaC coating was controlled to be 30 μm.

[0108] The results of Ta content in the TaC layer and the average particle size of TaC grains are shown in Table 1.

[0109] Table 1

[0110]

[0111] Note: * indicates the same as Example 1, and / indicates no oxygen or substantially no oxygen.

[0112] Test Case

[0113] The performance of the composite materials prepared in the examples and comparative examples was evaluated as follows:

[0114] (1) Thermal shock resistance evaluation

[0115] The experimental method for thermal shock resistance test is: heat the sample to be tested to 2000℃ at a heating rate of 10℃ / min, keep it warm for 1h, then use argon gas purge at 100L / min, air cool to 500±20℃, and then observe whether there are obvious cracks on the surface of the sample. After observing that there are no cracks on the surface, continue to heat it in the thermal shock furnace. If cracks appear, stop the test. Repeat this operation until cracking occurs. The result is expressed by the number of cycles when cracking occurs. For example, if the number of cycles is 45, it means that cracking occurs at the 45th cycle.

[0116] (2) Fracture toughness evaluation

[0117] According to the indentation method, the polished TaC coating sample is tested using a Vickers hardness tester with a pressure of 100 g in MPa.

[0118] The results are shown in Table 2.

[0119] Table 2

[0120]

[0121] It can be seen from the above data that, compared with Comparative Example 1, according to the method described in the present invention, using O source gas to introduce an oxygen-containing TaC layer between the substrate and the TaC coating can prepare a coating with good thermal shock resistance and fracture toughness.

[0122] From the comparison between the embodiment and comparative example 2, it can be seen that when the O element content in the deposition process is too high, the TaC grains will be too large, the fracture toughness of the coating will be greatly reduced, and the thermal shock resistance of the coating will be detrimental.

[0123] From the comparison between Example 1, Example 6 and Comparative Example 3, it can be seen that when the thickness ratio of the oxygen-containing TaC layer is controlled within a certain range, it is beneficial to control the particle size of the TaC coating within a reasonable range, and it is beneficial to obtain a TaC coating with high uniformity, which is beneficial to improving the thermal shock resistance and fracture toughness of the product.

[0124] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material, characterized in that: The method comprises the steps of sequentially chemically vapor depositing an oxygen-containing TaC coating and a TaC coating on a substrate surface to obtain the composite material; The gas system for depositing the oxygen-containing TaC coating comprises a Ta source, a C source, an O source, a reducing gas and a diluent gas, and the amount of the O source introduced is such that the oxygen content in the oxygen-containing TaC coating is less than 1000 ppm by weight; The conditions for depositing the oxygen-containing TaC coating include: a deposition temperature of 1100°C -1500°C and a pressure of 1 kPa -5 kPa; The gas system for depositing the TaC coating includes a Ta source, a C source, a reducing gas and a diluent gas; the conditions for depositing the TaC coating include: a deposition temperature of 1100° C. to 1500° C. and a pressure of 1 kPa to 5 kPa; The oxygen-containing TaC coating and the conditions for depositing the TaC coating are such that the oxygen-containing TaC coating accounts for 10-50% of the total thickness of the oxygen-containing TaC coating and the TaC coating.

2. The preparation method according to claim 1, characterized in that: The substrate is a carbon-based substrate; and / or The Ta source comprises at least one of TaF5, TaCl5 and TaBr5; and / or The C source comprises at least one of CH4, C2H4, C2H6, C3H6 and C3H8; and / or The O source comprises at least one of O2, H2O, CO2 and CO; and / or The reducing gas is H2; and / or The diluent gas is Ar or He.

3. The preparation method according to claim 1, characterized in that: In the gas system for depositing the oxygen-containing TaC coating and the gas system for depositing the TaC coating, the molar ratio of the Ta element to the C element is independently 1:1-2; and / or In the gas system for depositing the oxygen-containing TaC coating and the TaC coating, the molar ratio of the Ta source and the reducing gas is independently 1:0.5-5.

4. The preparation method according to claim 1, characterized in that: In the gas system for depositing the oxygen-containing TaC coating and the TaC coating, the molar ratio of the Ta source and the diluent gas is independently 1:10-100.

5. The preparation method according to claim 1, characterized in that: The conditions for depositing the oxygen-containing TaC coating also include: a deposition time of 0.5-2 hours.

6. The preparation method according to claim 1, characterized in that: The conditions for depositing the TaC coating also include: the deposition time is 2-4 hours.

7. A composite material, characterized in that The composite material is a composite material prepared by the preparation method according to any one of claims 1 to 6.

8. A composite material, characterized in that The composite material comprises a substrate and a composite coating located on the surface of the substrate, wherein the composite coating comprises an oxygen-containing TaC coating adjacent to the substrate and a TaC coating located on the other side of the oxygen-containing TaC coating; The oxygen content of the oxygen-containing TaC coating is less than 1000 ppm by weight; In the TaC coating, the average particle size of TaC grains is 10 μm-20 μm; and the oxygen-containing TaC coating accounts for 10-50% of the total thickness of the composite coating.

9. The composite material according to claim 8, characterized in that In the composite coating, the content of Ta element is 90wt%-95wt%; and / or The thickness of the composite coating is 20 μm-50 μm; and / or The oxygen content of the oxygen-containing TaC coating is 10 ppm to 200 ppm by weight; and / or The substrate is a carbon-based substrate.

10. Use of the composite material according to any one of claims 7 to 9 as a high temperature resistant material.